1996
DOI: 10.1073/pnas.93.18.9770
|View full text |Cite
|
Sign up to set email alerts
|

FHIT gene alterations in head and neck squamous cell carcinomas.

Abstract: To determine whether the FHIT gene at 3pl4.2 is altered in head and neck squamous cell carcinomas (HNSCC), we examined 26 HNSCC cell lines for deletions within the FHIT locus by Southern analysis, for allelic losses of specific exons FHIT by fluorescence in situ hybridization (FISH) and for integrity of FHIT transcripts. Three cell lines exhibited homozygous deletions within the FHIT gene, 55% (15/25) showed the presence of aberrant transcripts, and 65% (13/20) Head and neck cancers represent 3% of all canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
149
0
5

Year Published

1997
1997
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(165 citation statements)
references
References 17 publications
11
149
0
5
Order By: Relevance
“…It remains to be seen whether truncated TSG101 and FHIT transcripts are important in tumour progression in a wide variety of malignancies or whether these truncations are merely the consequence of altered mRNA splicing ®delity that occurs more commonly in tumour cells. In the case of FHIT, FISH and Southern blot analysis have shown that in some tumours and cell lines the same exons that are missing from the truncated transcripts appear to be deleted in genomic DNA Virgilio et al, 1996). Despite this, it has not been possible to clone any of the putative genomic breakpoints and so the evidence that FHIT is the real target of the genomic deletions seen at the fragile site locus that encompasses this gene is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…It remains to be seen whether truncated TSG101 and FHIT transcripts are important in tumour progression in a wide variety of malignancies or whether these truncations are merely the consequence of altered mRNA splicing ®delity that occurs more commonly in tumour cells. In the case of FHIT, FISH and Southern blot analysis have shown that in some tumours and cell lines the same exons that are missing from the truncated transcripts appear to be deleted in genomic DNA Virgilio et al, 1996). Despite this, it has not been possible to clone any of the putative genomic breakpoints and so the evidence that FHIT is the real target of the genomic deletions seen at the fragile site locus that encompasses this gene is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…The noncoding exon 4 of the FHIT gene is distal to the marker D3S1481 (Figure 1). Aberrant transcripts of this gene were detected in several di erent digestive tract cancers (50%) , lung tumors both SCLC (80%) and NSCLC (40%) (Sozzi et al, 1996a), in 57% of Merkel cell carcinoma (Sozzi et al, 1996b), in 20% of breast cancers , and more recently in 55% of squamous cell carcinoma of the head and neck (Virgilio et al, 1996). Sequence analysis of the RT-PCR rescued transcripts of the FHIT gene revealed that in all cases complete exons were lost.…”
Section: Introductionmentioning
confidence: 99%
“…Representational di erence analysis demonstrated a frequent site of homozygous deletion at the FHIT locus in esophageal, gastric and colorectal carcinomas (Lisitsyn et al, 1994). Several recent papers have reported alterations of FHIT in several tumor types, frequently characterized by abnormal-sized transcripts (Virgilio et al, 1996;Sozzi et al, 1996;Yanagisawa et al, 1996;Mao et al, 1996;Ohta et al, 1996;Druck et al, 1997). However, some investigators have found a completely normal FHIT transcript and coding DNA sequence in colorectal carcinoma cell lines and xenografts, suggesting either a di erent inactivation mechanism or a minor role for FHIT in the genesis of colorectal cancer (Thiagalingam et al, 1996).…”
Section: Introductionmentioning
confidence: 99%